The loading characteristics of bulk coal in the middle trough and its influence on rigid body parts - Zhang, Peilin (Strojniški vestnik, 2020)
The working reliability of a scraper conveyor is related to the bulk coal load characteristics and the interaction between rigid body parts and bulk coal. In the existing relevant research, a load of coal on rigid body parts is equivalent to constant central acting on some points, ignoring time-varying and uneven distribution of the load and new load generated by the interaction, which results in some load characteristics and related faults being obscured. In this paper, the rigid-discrete coupling simulation model of scraper conveyor is established based on the discrete element method and the multi-body dynamic method, and the overall compressive force gradient distribution of bulk coal in the middle trough, the violent interaction between bulk coal and rigid body parts, and the clamping stagnation of scrapers are studied. The results show that the bulk coal compressive force has an obvious distribution gradient in the chute, and in the chute between two scrapers, the bulk compressive force in the first half is about 19 % of that in the second half in the y-direction. The coal particles stuck between the scrapers, the vertical chainrings, and the middle plates violently interact with the rigid body parts, and the coal particles average compressive force is 59 times that of other coal particles. The scraper influenced by bulk coal is easily stuck at the connection of two chutes, and the tension of the chain before the scraper increases sharply, and the maximum tension of the chainrings is about three times that of the maximum contact force between the scraper and the chute.
Keywords: compressive force distribution gradient; dinamika več teles; discrete element method; gradient porazdelitve tlačne sile; metoda diskretnih elementov; močna interakcija; multi-body dynamics; scraper conveyor; strgalni transporter; violent interaction